siRNA Library Screening Identifies a Druggable Immune-Signature Driving Esophageal Adenocarcinoma Cell Growth - Reynolds, John; Long, Aideen; Duggan, Shane P.; Garry, Catherine; Behan, Fiona; Phipps, Sinead; Kudo, Hiromi; Kirca, Murat; Zaheer, Abdul; McGarrigle, Sarah; Goldin, Robert; Kalloger, Steve E.; et al. (My University, 2018)
This study de fi nes immune-associated factors supportive of esophageal adenocarcinoma cell growth through small interfering RNA screening and pathologic and functional studies. Fostamatinib R788, targeting Janus kinase/signal transducer-and-activator of transcription and TYRO protein tyrosine kinase binding protein/spleen tyrosine kinase/AKT serine-threonine kinase pathways, induced esophageal adenocarcinoma cell death and reduced tumor burden in xenografted mice.
Keywords: Immune-associated factors; Esophageal Adenocarcinoma; Barrett's esophagus; Inflammation; Therapeutic targets